Análisis del control interno en la Empresa Cabrera Cabrera S.A. COMCABSA - Vaca Muñoz, Cesar Augusto (2021)
The present case study is carried out at Empresa Cabrera Cabrera S.A. COMCABSA, a private company belonging to Mr. Lindon Antonio Cabrera Cabrera as legal representative, is located in Ventanas, located in Velasco Ibarra streets between Av. Seminario and Bolívar, to know how the internal control of the company is carried out, which has been affected by problems such as, organizational communication, work environment, teamwork, control of entries and exits, among other negative factors that directly affect the employees that work in the institution and therefore the effective and efficient performance of the same.